Sentiment Analysis on Twitter(X) Related to Relocating the National Capital using the IndoBERT Method using Extraction Features of Chi-Square - Arista, Dufha; Sibaroni, Yuliant; Prasetyo, Sri Suryani (Universitas Budi Darma, 2024)
Sentiment analysis or commonly referred to as opinion mining is a field of science that can be used to get the percentage of positive sentiment and negative sentiment towards a person, company, institution, product, or even an issue or topic. Various topics are discussed on social media, one of which is Twitter (X). Starting from the economy, politics, social, culture, law and others. One of the most discussed topics on Twitter (X) is the transfer of Indonesia's capital city to East Kalimantan Province, which has drawn various opinions from netizens on Twitter (X). In this study, data regarding the transfer of the national capital taken by the author was taken from social media, namely from the social media Twitter (X) with a date range of January 1, 2022 to February 28, 2022. The method used in this research is IndoBERT using Chi-Square. Based on the experiments that have been carried out, the performance of IndoBERT with Chi-square selection features shows good results with an overall accuracy value of 94%, a precision value of 85%, a recall value of 91%, and an f1 value of 88.4% for all datasets.